Editor’s Note - Elizabeth Hubbard (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Educating the next generation of orthopaedic surgeons is one of the privileges of working with medical students, residents, and fellows. As medical training has changed, simulation training has played a greater role in helping learners gain the technical skills associated with our job independent from the clinical environment. More and more programs are creating educational curricula that revolves around surgical simulation to supplement the experience their trainees receive in the clinic or the OR. However, for younger educators or those associated with education programs that have limited resources, it can be difficult to know where to begin when it comes to either building or expanding a surgical simulation component to a residency or fellowship. In light of this, our goal was to reach out to surgeons and educators who have taken a leading role in developing simulation training experiences. The goal of this edition is (1) to offer recommendations for how to begin incorporating simulation training into your educational program, (2) to provide detailed examples of simulation training exercises being implemented across North America, and (3) to reflect on the current state of medical trainee education and thoughts on how, as a society, we can continue to improve medical training. To our readers—We have compiled educational techniques that range from inexpensive, low fidelity models to models that are both high fidelity and utilize cutting-edge technology. Our hope is that you will be able to choose one or more of these to incorporate into your teaching and that you may be inspired to use them as a foundation for enhancing your own skills program. To each of our authors—I would like to thank all of you for your willingness and enthusiasm to share your educational techniques and thought pieces. In reviewing and editing these articles, I have been inspired by your dedication to resident and fellow education and your enthusiasm for finding new ways to introduce learners to our fields. I would also like to thank Ken Noonan, MD, who was the originator of this project and who played an integral role in securing authors and shaping the entire edition; Lisa DuShane, who kept everything organized and was always ready with an answer to any of my questions; as well as Bryan Tompkins, MD; Tara Long; Kaitlyn Petrando; and Teri Stech for all of their help.